Pemanfaatan Soft Power Amerika Serikat dalam MengintimidasiOtokrasi Korea Utara, Studi Kasus: Film The Interview (2014) - Nisya Amalia Agusti (Indonesian Student Association Study Center in Türkiye, 2025)
A contentious Hollywood action-comedy film became a hot topic in 2014, sparking an increase of hostilities between the two countries, the United States and the Democratic People's Republic of Korea. In an era when tensions between liberalism and communism are lower than were during the Cold War, this film's reappearance raises a sensitive issue between those two countries. The United States uses its dominance in the global entertainment industry through numerous its film productions that are in high demand by the global community as a type of soft power diplomacy to intimidate its political/idealist adversaries and influence global public opinion to support it. Propaganda through communication media such as posters, radio, television, movies, music, and even social media posts like today has been commonly used since World War I to mobilize public opinion in supporting or justifying an international actor's interests. Although its performance is not as fast as hard power, it can influence and encouraging decision makers or countries to place their positions in international relations, even leading them to use hard power as final output to support these interests. Through constructivism and using film The Interview as a case study. this research paper aims to analyze and describe the utilization soft power on propaganda by the U.S.' to intimidate its political/idealism rival, North Korea with its autocracy.